Spatiotemporal development of national botanic gardens worldwide and their contributions to plant diversity conservation from 1593 to 2023 - Li, Yiyi; Li, Shidong; Zhao, Guangshuai (Frontiers in Forests and Global Change, 2023)
The national botanic garden is not only a primary means of global ex situ conservation but also a key indicator of biodiversity conservation capacity in a country. To understand the contributions of national botanic gardens from around the world to plant diversity conservation, we generated a long time-series dataset to investigate the spatiotemporal development of national botanic gardens and then explored their functional expansion from 1593 to 2023. The results showed that the development of national botanic gardens was driven by the development demands of human society and could be divided into three stages, i.e., the initial exploration stage of early botanic gardens (1593–1765), the colonial development stage of modern botanic gardens (1765–1945), and the rapid development stage of modern botanic gardens (1945–2023). The first national botanic garden was established in Western Europe, followed by other national botanic gardens being established in the rest of the world. The functions of national botanic gardens evolved from the collection of medicinal and plant resources to multiple purposes, including scientific research, plant diversity conservation, education, and dissemination of knowledge. Contemporary national botanical gardens have played a crucial role in plant diversity conservation and scientific research on the response and adaptation of plant diversity to global change. Future development and management of national botanic gardens will play a crucial role in achieving future targets of the post-2020 global biodiversity framework, which meets the UN Sustainable Development Goals.